Handbook of hazardous chemical properties - Cheremisinoff, Nicholas P. (Boston : Butterworth-Heinemann, 2000)
This book provides information on nearly 700 chemicals of commercial and industrial importance, as well as health (toxicological) and safety handling information. It provides chemical specific information pertinent to safe handling and transportation of chemicals, worker protection, emergency response information to address spills, explosions on fire situations, and chemical stability/reactivity data. It is designed as a standard reference handbook for chemical engineers, safety engineers, toxicologists, fire safety specialists, chemists, laboratory and plant technicians.
Preface; Abbreviations: Dozens of specific chemicals alphabetically arranged; Glossary of Terms; Hazardous Chemical Property Entries: For each Chemical Designation Entry there are five data fields: Observable Charateristics, Physical and Chemical Properties, Health Hazards Information, Fire Hazards, Chemical Reactivity; Synonyms Index.
Includes index.
Keywords: Toxicology -- Handbooks, manuals, etc; Chemicals -- Safety measures -- Handbooks, manuals, etc; Hazardous substances -- Handbooks, manuals, etc; Industrial safety -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc